Why Women Diagnosed with Gestational Diabetes Mellitus Undergo a Medical Check Up One-year Post-childbirth - Watai, Izumi; Ito, Yukie; Tatsumi, Asami (Japanese Journal of Public Health Nursing, 2022)
Objective: This study aimed to clarify the reasons women diagnosed with gestational diabetes mellitus (GDM) undergo a medical check-up one year post-childbirth.Methods: Semi-structured interviews were conducted with women diagnosed with GDM when they came to the hospital or outpatient clinic to undergo a medical check-up one year post-childbirth. The collected data were analyzed qualitatively.Results: Thirteen women participated in the study. The results were aggregated into 18 categories with six primary categories. The six primary reasons reported by participants for receiving medical check-ups were: (1) I want to avoid becoming diabetic; (2) I understand that medical check-ups should continue after childbirth; (3) A medical check-up is an opportunity to review overall health and lifestyle; (4) I want to be reassured by advice from a doctor; (5) Others recommended that I have a medical check-up; and (6) There are social conditions for available medical check-ups even while raising children.Discussion: Women diagnosed with GDM continued to undergo medical check-ups after childbirth to protect their own health for reasons that included explanations from medical staff, concern for their children, social availability of medical care during the child-raising years, and recommendations from others. These reasons were effective in ensuring continuous medical check-ups.